Factors Of Reflexive Approach Implementation In Teaching English (Eurasian Research Bulletin, 2023)
Teaching foreign languages is always at the forefront of modern educational trends, and the problem of forming reflective thinking in teaching foreign languages is no exception. will be interesting and useful for English language teachers and will help their students develop the important concept of “language learning awareness” for learning a foreign language.